Awareness of Personal Protective Equipment Among Laboratory Workers in Tertiary Health Centre, Ibadan - Amoo, Abimbola; Ezoke, Christiana (International Journal of Infection Prevention, 2020)
Introduction Health care personnel are exposed to a variety of material occupational health hazards while handling biological material and contaminated equipment. The use of appropriate and good qualitypersonal protective equipment in work places cannot be over emphasized. Several years ago, this need was highlighted to several physicians like Sir Thomas Morrison Legye. He identified the role of the employer of labour and those of the employee in reducing workplace hazards and consequently achieving a healthy workplace environment. Objectives This study was to determine level of awareness and utilization of Personal Protective Equipment among Medical Laboratory workers. Methods A questionnaire was structured with two sections and a total of 92 were administered. A pilot study was also carried out before the administration of the questionnaire. The data collected was analyzed on Microsoft excel spreadsheet in duplicate. It was then exported into EPI info version 3.4.1. Data was presented using frequency tables and chi square. Results About 77.3%, 72.9%, and 72.7% were aware of the use of goggle, gloves, and importance of hand washing in preventing exposure to Healthcare associated infections while working on patients’ samples. However, under the socio- demographic characteristics of the respondents and awareness level at P-value < 0.5 the results were 0.02. 0.5, 0.85, 0.92 for education, gender, years in service and age respectively. Hence, there is no significant relationship between respondents’ gender, age and year in service, and level of awareness. Conclusion The hospital management should ensure regular provision and supply of Personal Protective Equipment (PPE) to ensure continual usage. Also, regular training and re-training should be conducted to keep the laboratory workers at briefs with latest innovative and benefits of PPE developments to this end.
Keywords: Healthcare Associated Infections; Cross Infection; Personal Protective Equipment